Serawai sebagai bahasa minoritas (sebuah kajian ekolinguistik dalam pembelajaran dan pemertahanan) - Andestend, Andestend; Asmahasana, Salati; Pebriani, Luzi; Shaliha, Gita Putri Amalia (Universitas Mulawarman, 2024)
The purpose of this research is to analyze the role of the environment in the learning and preservation of the Serawai language, also known as ecolinguistics. A qualitative approach with a descriptive method is used in this research to describe the result of the interview and observation of the Serawai language. The subject of this research is a group of Serawai speakers who live in Bogor. The instrument of this research is the interview. Data analysis was conducted through five stages, namely data collection, data reduction, data grouping, data analysis, and conclusion drawing. The results showed that the user community still uses the Serawai language, but it is expected to experience a shift or even extinction. It is caused by the decreasing use of the Serawai language and the lack of Serawai language learning for children. Environmental factors also play an important role in the formation of Serawai language conversation, but the influence is limited. Children who live in a Serawai language environment tend to become bilingual or even multilingual because the learning environment is also multilingual. In addition, parents are also less serious about teaching the Serawai language; some even switch to other languages.